Effect of oxygenated treatment on corrosion of the whole steam–water system in supercritical power plant. (25th January 2016) - Jiang, Dongfang; Xu, Hong; Deng, Bo; Li, Mengyuan; Xiao, Zhuonan; Zhang, Naiqiang
Highlights: Corrosion experiments with different dissolved oxygen contents are carried out. The influence of dissolved oxygen on the whole steam–water system is distinguished. A more effective feedwater chemistry treatment method is proposed. Abstract: The feedwater chemistry is critical to the overall corrosion and reliability of the fossil fired generating units. The effect of dissolved oxygen on corrosion of carbon steels in feedwater system is analyzed. The corrosion experiments of boiler tube steels in supercritical water containing different dissolved oxygen are carried out. The different effect mechanics of dissolved oxygen on corrosion in different parts of steam–water system are defined. Flow accelerated corrosion in low temperature feedwater system can be controlled by dissolved oxygen, but dissolved oxygen can accelerate failure of boiler tubes at high temperature from three aspects: corrosion rate, crack growth rate of SCC, and evaporating consumption rate of chromium. Considering the corrosion of the whole steam–water system, a more effective feedwater chemistry treatment method is proposed.